Free Space Optical Communication: System Design, Modeling, Characterization and Dealing with Turbulence - Raj, A. Arockia Bazil (De Gruyter, 2015)
Recent progress in ICT has exceeded our expectations for meeting the requirement of multimedia society in the 21st century. The FSOC is considered to be one of the key technologies for realizing very high speed multi GbPs large-capacity terrestrial and aerospace communications. In FSOC, the optical beam propagation in the turbulent atmosphere is severely affected by various factors suspended in the channel. Wavefront aberration correcting with continuous beam alignment are the key requirements for a successful installation of an FSOC system which are the main contributions in our book. Establishment of FSOC setups, development of accurate weather station, measurement of atmospheric attenuation (Att) and turbulence strength (Cn2), development of new models to predict the Att and Cn2, design of Response Surface Model and Artificial Neural Network based on controller, implementation of neural-controller in FPGA and attaining the BER of 6.4x10^-9 during different outdoor environments. All the original contributions, newness, findings and experimental results etc., are reported in the book. Subject of work; Wireless Optical Communication. The content of the book can be referred by various application designers and/or academicians for working on FSOC transceiver design, laser cutting, laser metrology, laser surgery, beam focusing & pointing, beacon positioning and coupling etc. Further, all necessary MATLAB and VHDL codes are also given on appropriate pages for the readers' quick/ clear understanding.